The university library of the Demidov Lyceum in Yaroslavl - A. A. Soloviev (Высшее образование в России)
The article is devoted to the origin and development of the fundamental library of Demidov Law Lyceum in Yaroslavl. Earlier there were practically no publications on its activity. The qualitative and quantitative structure of library fund is analyzed. Persons who have made a significant contribution to the formation and development of the library are named.